(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article analyzes the main forms of monitoring students’ knowledge, skills and abilities in the process of teaching mathematics, their didactic significance and role in increasing educational efficiency. It also discusses oral, written, test, practical and modern digital forms of monitoring. It is substantiated that the educational process can be effectively organized through regular assessment of students’ knowledge.